Predictive Genetic Testing in Children: Constitutional Mismatch Repair Deficiency Cancer Predisposing Syndrome. Issue 2 (15th October 2013) - Bruwer, Zandrè; Algar, Ursula; Vorster, Alvera; Fieggen, Karen; Davidson, Alan; Goldberg, Paul; Wainwright, Helen; Ramesar, Rajkumar
Abstract: Biallelic germline mutations in mismatch repair genes predispose to constitutional mismatch repair deficiency syndrome (CMMR‐D). The condition is characterized by a broad spectrum of early‐onset tumors, including hematological, brain and bowel and is frequently associated with features of Neurofibromatosis type 1. Few definitive screening recommendations have been suggested and no published reports have described predictive testing. We report on the first case of predictive testing for CMMR‐D following the identification of two non‐consanguineous parents, with the same heterozygous mutation in MLH1 : c.1528C > T. The genetic counseling offered to the family, for their two at‐risk daughters, is discussed with a focus on the ethical considerations of testing children for known cancer‐causing variants. The challenges that are encountered when reporting on heterozygosity in a child younger than 18 years (disclosure of carrier status and risk for Lynch syndrome), when discovered during testing for homozygosity, are addressed. In addition, the identification of CMMR‐D in a three year old, and the recommended clinical surveillance that was proposed for this individual is discussed. Despite predictive testing and presymptomatic screening, the sudden death of the child with CMMR‐D syndrome occurred 6 months after her last surveillance MRI. This report further highlights the difficulty of developing guidelines, as a result of the rarity of cases and diversity of presentation.